Evaluation of the prevalence and intensity of caries in children with rheumatism. - Kazakova N.N; Sadieva D.Sh; Khamrayeva Sh.F (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Preservation and strengthening of the dental health of the population is one of the strategic directions of medicine. Despite modern scientific achievements, the intensity and prevalence of caries, as well as periodontal tissue diseases, have always been high. One of the important factors in the development of periodontal hard tissue diseases are systemic somatic diseases of the body. Rheumatism or acute rheumatic fever is a disease characterized by widespread inflammation of the connective tissue, mainly due to streptococcal infection. The disease most often occurs in children aged 7-15 years.